"Life…in the midst of death": Notes on the Relationship Between Slave Insurance, Life Insurance and Disability - Ralph, Michael (Disability Studies Quarterly, 2012)
This article examines the way post-bellum genres of disability, race, and credit-debt shaped the emergence of US slave insurance and life insurance industries. After all, the same period which witnessed the demise of formal enslavement saw the debut of structures that protected the privilege of people whose wealth and power threatened to come undone: this would include sharecropping and convict leasing. Despite a similar emphasis on institutionalizing credit-debt relations, insurance appears benign by comparison. Even though insurance agencies assign differential value to human lives, the birth of insurance is seen, along with the triumph of capitalism and democracy, as part of the birth of freedom. In what follows, I explore a discourse on debility that was likewise a discourse on debt—one with enduring resonance for social movement politics. Keywords: disability, civil rights, social movement politics, slavery, capitalism